Solve for w 3(w+2)-w=2(w-1)+5

Math
3(w+2)-w=2(w-1)+5
Simplify 3(w+2)-w.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
3w+3⋅2-w=2(w-1)+5
Multiply 3 by 2.
3w+6-w=2(w-1)+5
3w+6-w=2(w-1)+5
Subtract w from 3w.
2w+6=2(w-1)+5
2w+6=2(w-1)+5
Simplify 2(w-1)+5.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
2w+6=2w+2⋅-1+5
Multiply 2 by -1.
2w+6=2w-2+5
2w+6=2w-2+5
Add -2 and 5.
2w+6=2w+3
2w+6=2w+3
Move all terms containing w to the left side of the equation.
Tap for more steps…
Subtract 2w from both sides of the equation.
2w+6-2w=3
Combine the opposite terms in 2w+6-2w.
Tap for more steps…
Subtract 2w from 2w.
0+6=3
Add 0 and 6.
6=3
6=3
6=3
Since 6≠3, there are no solutions.
No solution
Solve for w 3(w+2)-w=2(w-1)+5

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top